Особливості побудови інтервальної системи алгебричних рівнянь та методу її розв’язку в задачах ідентифікації лінійного інтервального різницевого оператора - Дивак, М.П.; Дивак, Т.М. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
The task of identification of linear interval difference functional is considered. This is the task of solving of interval system of nonlinear algebraic equations is proofed. Properties of solutions of this system and approaches for designing of algorithms of its solving are researched.